Activated carbon derived from bamboo waste (B. vulgaris and G. albociliata) using potassium hydroxide as an adsorbent for the removal of heavy metals and dyes / Siti Suhana Hassan - Hassan, Siti Suhana (2023)
Water pollution is worsening and increasing the threat to humans due to the toxic heavy metals and dyes discharged from industrial activities and urbanizations. Due to that, wastewater treatment is required to ensure the safety and cleanliness of the water for general use. The adsorption process by activated carbon is a common method used to treat water pollution. Activated carbon has wide applications and advantages. Its demand has increased significantly, especially in removing heavy metals and dyes in wastewater treatment. This is due to its simple applications, environmentally friendly, and high efficiency. However, commercial activated carbon is rather expensive. Agricultural waste with non-economic value provides cheaper production costs for activated carbon production, especially bamboo waste. Bamboo waste is a much cheaper, fast-growing, and sustainable resource. Furthermore, it is also abundantly available in Malaysia. Therefore, producing activated carbon derived from agricultural sources provides a better alternative. As such, local bamboo species from Bambusa vulgaris and Gigantochloa albociliata were used in this study to produce activated carbon. The bamboo charcoal was chemically impregnated with KOH as an activating agent in a 1:1, 1:2, and 1:3 ratio and activated in the muffle furnace at 500 °C and 600 °C. The heavy metals and dyes were removed using AAS for heavy metals and UV-Vis for dyes, respectively. The activated carbon produced was characterized by surface functional groups (FTIR) and morphology (SEM). Their IR spectrum indicates essential functional groups for the adsorption process. The SEM images of the activated carbon produced show apparent porosity on the activated carbon surface that enhances the removal process. Both B. vulgaris and G. albociliata activated carbon showed excellent performance in removing Zn, Fe, Ni, Cr, MB, and MO, up to 99.9 % of Zn removal.